Global Collaboration: Making a Difference for Mothers and Babies. Issue 2 (March 2021) - Callister, Lynn Clark
Abstract : Global partnerships that offer clinical simulation and education for nurses, midwives, physicians, and community health workers around the world promote safe outcomes for mothers and babies. Our global health and nursing expert, Dr. Callister, discusses some of the recently published literature about global partnerships for maternity care.